Land-use history and the origins and effects of lianas on tree-communities.: The case of secondary forests in Northeastern Yucatan Peninsula, Mexico - Garrido-Pérez, Edgardo I.; Gerold, Gerhard (ERDKUNDE, 2009)
Economic problems generate large secondary tropical forests due to crop abandonment; lianas (woody vines climbing upon trees) proliferate there. Lianas generally retard the growth and carbon capture of trees, potentially enhancing global change. It is not known whether all liana species play such a role and which land-use disturbances determined the current species composition of liana communities. We surveyed all lianas 1cm diameter at ground level and all trees 3.16 cm diameter at 1.3 m above ground in twelve plots 20 x 20-m each in semi-evergreen tropical forests in Northeastern Yucatan Peninsula, Mexico, re-measuring the trees 15 mo later. Lianas were classified into two anatomic types: “hard” (typical stem with compact xylem masses) and “soft” (with much parenchyma and wide xylem vessels). History, archaeology, anthropology, and remote sensing studies, as well as non-formal interviews were used to determine the land-use history of each stand. Increasing densities of the hard liana Dalbergia glabra (Leguminosae), but not of soft lianas –Arrabidaea spp, Cydista sp, Melloa spp (Bignoniaceae) and Serjania sp (Sapindaceae), were related to more rapid relative growth rates of trees (Linear regression, R2 = 0.680, P = 0.001). Where D. glabra dominated, the trees hosting it grew more rapidly, but trees with large liana-tangles grew more slowly where soft lianas were dominant (Kruskall Wallis, P > 0.01 in both cases). The anatomy of soft lianas suggests that they are less able to survive burn after slash during shifting cultivation than D. glabra – the previous land use where D. glabra dominated. Soft-liana dominated stands were not burnt but subjected to liana-cut during logging and extraction of lianas, palm leaves and latex from Manilkara zapota trees. Our results suggest that some lianas enhance carbon capture mitigating global change, whereas others do not and that the dominance of one liana species is a legacy of previous land use, which is better understood by combining natural and social sciences.